Nonlinear dependence between the US banking and insurance market during COVID-19 epidemic - Moraes, Rodrigo Rodrigues Branco de (2022)
We propose a multivariate stochastic volatility-double jump model to capture the presence of jumps in mean, and conditional variance in the returns assets of the nine largest North American banks by market capitalization and nine of the most relevant North American insurance companies were considered during the period from the beginning of march 2020, when starts the COVID-19, to mid-2021. We divide ours samples in three different groups, a group with insurance companies only, another with banks and one with all eighteen companies assets. For all the three samples, the common factors estimated shows enough precision to capture characteristics and stylized facts of these financial series in a period of crisis in the stock market, such as jumps in mean, volatility and conditional volatility.